The Role of Family Medicine Supervisors with Compliance with Medication in Tuberculosis Patients Aged 45 to 60 Years in the Pace Community Health Center Area, Nganjuk Regency - Priyanto, Kurniawan Edi; Rossana Rhisky Ambardewi (Journal of Global Research in Public Health, 2025)
PMO plays a very important role in the treatment of pulmonary TB patients. One of the factors that affects compliance with pulmonary TB treatment is the fairly long treatment period, so that many patients feel cured and stop taking their medication. Non-compliance with treatment causes a high rate of treatment failure in pulmonary TB patients. The purpose of this study was to analyze the relationship between the role of medication supervisors and medication compliance in tuberculosis patients aged 45 to 60 years. The design used in this study was Cross Sectional with a simple random sampling technique of 44 respondents. Data was obtained from filling out a questionnaire. The results of the study found that in measuring the Role of Family PMOs that almost all respondents had an active family PMO role with a prevalence of 81.81% of 36 respondents, and in Medication Compliance, it was found that almost all respondents were compliant with taking medication with a prevalence of 77.27% of 34 respondents. The results of the Chi-Square Test statistical test found a value (p <0.05) it can be said that there is a Relationship Between the Role of Family Medication Supervisors and Medication Compliance in Tuberculosis Patients Aged 45 to 60 Years. Meanwhile, the contingency coefficient value of 0.293 shows a relationship between variables, but its strength is not too strong (the coefficient value is close to 0.3). If the role of the Family PMO is carried out well, TB patients have a great chance of completing treatment without obstacles and reducing the risk of complications.